(untitled) - Andreasen, J O (Copenhagen, Denmark, 1990)
The book provides dental practice or emergency service of a hospital, with a readily accessible guide to initial treatment of acute dental trauma. Appendix 1 provides a standardized emergency chart that can be used. Moreover, Appendix 2 provides a standardized clinical examination form for acute and follow-up examinations. Appendix 3 summarizes the clinical and radiographic characteristics of each luxation category. It is suggested that these or similar forms be duplicated and completed as an integral part of trauma patient's record. In the case of some trauma entities, such as concussion, subluxation and some injuries to the primary dentition, observation "therapy" is the only treatment needed. Techniques for the reduction of tooth dislocations include immediate repositioning or repositioning using an orthodontic or surgical approach. Finally Appendix 4 is aimed at assisting in determining when the patient should be seen in order to detect changes in the follow-up period which might necessitate interceptive therapy
Keywords: Dental surveys,Dental therapeutics,Dentistry,Periodontium; Aesthetics,Injuries